Development of a standardized method for rice neck blast inoculation - Mirnia, Eka; Carvajal, Raphael; Ortega, Kendrix; Pangga, Ireneo; Castilla, Nancy (International Rice Research Institute, 2024)
Rice blast disease caused by Magnaporthe oryzae B.C. Couch causes significant yield losses in rice production globally. Despite its economic importance, the epidemiology of neck blast is not well understood which could be partly attributed to the absence of a reliable and standardized method for inoculating the neck with the pathogen. This study was conducted to develop a reliable and replicable method for inoculating the rice neck with the blast pathogen. The method was developed based on ten replicated experiments conducted in a greenhouse at the International Rice Research Institute (IRRI) 2018 to 2020. The results showed that the injecting the spore suspension into the neck is the most effective delivery method, followed by pricking the neck and then wrapping it with cotton soaked in spore suspension, brushing the neck with spore suspension, wrapping the non-pricked neck with cotton soaked in spore suspension, and spraying. The injection method and spore concentration of 1 x 105 spores/ml resulted in higher neck blast incidence, longer lesion and relative lesion length, and shorter incubation period compared to the other treatments. The best inoculation method is injection on Co39 or NSIC Rc216 variety using the following components: downward direction of injection, 1 x 105 spores/ml spore concentration, 0.25 mm x 8 mm needle size, 0.3 ml volume, and inoculation at heading stage. Additional experiments will be conducted at IRRI to improve the inoculation method developed in this research. The effect of growth stage on the efficacy of the injection method will be evaluated to optimize the timing of its application. The growth stages to be considered are heading, flowering and milk because infection at these stages affect neck blast incidence under natural conditions.